A hybrid active neutral point clamped inverter utilizing Si and Ga2O3 semiconductors: Modelling and performance analysis - Meraj, S.T. (MDPI, 2021)
In this paper, the performance of an active neutral point clamped (ANPC) inverter is eval-uated, which is developed utilizing both silicon (Si) and gallium trioxide (Ga2O3) devices. The hy-bridization of semiconductor devices is performed since the production volume and fabrication of ultra-wide bandgap (UWBG) semiconductors are still in the early-stage, and they are highly expen-sive. In the proposed ANPC topology, the Si devices are operated at a low switching frequency, while the Ga2O3 switches are operated at a higher switching frequency. The proposed ANPC miti-gates the fault current in the switching devices which are prevalent in conventional ANPCs. The proposed ANPC is developed by applying a specified modulation technique and an intelligent switching arrangement, which has further improved its performance by optimizing the loss distri-bution among the Si/Ga2O3 devices and thus effectively increases the overall efficiency of the in-verter. It profoundly reduces the common mode current stress on the switches and thus generates a lower common-mode voltage on the output. It can also operate at a broad range of power factors. The paper extensively analyzed the switching performance of UWBG semiconductor (Ga2O3) devices using double pulse testing (DPT) and proper simulation results. The proposed inverter reduced the fault current to 52 A and achieved a maximum efficiency of 99.1. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.